Use of Technology in Industry 4.0 to support the fight against the COVID-19 epidemic through a hand hygiene dispenser using locally built devices (Latin-American Journal of Computing, 2020)
The outbreak of COVID-19 pandemic promoted the existence of new issues. They should have been quickly solved.  The solutions have been promoted without all the available resources because lockdown and several restrictions that were established. This paper proposes an innovative idea with the development to get a functional prototype. The prototype allows the sanitation of hands.  This process is gathered employing liquids that have alcohol. The dispenser does not require the direct contact of the user with the prototype. This is adapted to Ecuadorian reality and could be produced with local parts. We present the challenges that were solved to have a product that complete works. It includes the design of sensing and actuation devices that are chosen to achieve the projected goals.  The control structure and the recommendations for correct usage are also presented. Finally, the proposals to have a better prototype with internet of things (IoT) are introduced.